KEBIJAKAN HUKUM PIDANA DALAM PERTANGGUNGJAWABAN KORPORASI DI BIDANG KETENAGAKERJAAN (Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan) - Eric Prima Setiawan (JURNAL AKTA YUDISIA, 2019)
Abstract The development process of modernization shows that corporations play an important role in society. However, in achieving the goals and interests, corporations occasionally commit acts in violation of the law and result in the victim suffering a loss. Corporations in the field of labor also commit offenses or crimes in the form of actions that ignore the security and safety of laborers. It means that the corporation has ignored the interest of the laborers. Act No. 13 of 2003 on Labor is the legal basis for the laborers. Therefore it is necessary to make unequi vocal and explicit arrangements about corporations’ liability in general within the act. The method used in this thesis is a normative juridical with a conceptual and legislation approach. Act No. 13 of 2003 on Labor still has not regulate explicitly the corporations’ liability to the victims of corporations’ crime. It is because there is no specific regulation on sanctions replacement if the corporation does not pay the principal financial penalties imposed and there is no provision governing when a corporation does not meet its obligations to pay for the rights and/or compensation to laborers. The effort of ius constituendum related to corporations' liability is to en act a separate regulation expressly and explicitly regarding corporations' liability in general within the act. Thus, the criminal law policy of corporations' liability in the field of labor can be realized.Keywords : Corporate, Corporations’ Liability, Labor.